Формирователи импульсов тока для контактной сварки - Paerand, Yu. E.; Bondarenko, Yu. V.; Bondarenko, A. F. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
An analysis and generalization of the principles of designing current pulse shapers for spot welding has been carried out, taking into account modern trends in its development. The main features have been identified, and a contemporary classification of devices has been compiled. Using the proposed classification scheme, the most promising principle for constructing pulse shapers for micro-welding has been highlighted — a transformerless pulse shaper with energy accumulation based on transistor regulators operating in active mode.